FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU PETANI DALAM MENERIMA PROGRAM KAWASAN RUMAH PANGAN LESTARI (KRPL) DI KABUPATEN PELALAWAN - Rahmi Puspita Sari; Rosnita Rosnita; Roza Yulida (Universitas Sebelas Maret, 2016)
The aims of this research are: (1) To determine the implementation of KRPL Programs, (2) To analyzing dominant indicator and influence of characteristic of innovation, communication channels, agent of change, community leaders and characteristic farmers. The research was conducted in 11 villages of Pelalawan Regency in 2013. The population is manager and members of farmers as 360 people which were taken 174 people as samples. The method used is descriptive analysis and Structural Equation Models (SEM). The research showed implemention of KRPL program in Pelalawan regency accepted Rp. 47.000.00 for each group. The coast was spent for environment industry like the source of food or cattle and fish.The most dominant indicator that influences characteristic of innovation is concord of program, for communication channel is social media, for agent of change is keep the program and prevent it from any sticking, for community leaders is to educator and the characteristic of farmer is subsistence level. Farmers habit in deciding the dominant is using confirmation step. The most influent variable of farmers habit is characteristic innovation.